(untitled) (Scientific journal of the Fergana State University, 2024)
The article analyzes a literary work capable of influencing human thinking and striving for new heights of development. T. Murod’s work fully reveals age-old traditions, reflects national customs and identity. Involvement in the novel causes delight, lively discussion of the plot, acquaintance with the skill of the author, which reflects the high level of talent of the master of the word. The characters of the characters of one of T. Murod’s novels called “The Field inherited from the father”, where the narration is conducted on behalf of one of the characters, are considered. The characters of the novel serve as a means of forming and expressing an artistic vision of the world. Events are considered as a result of the influence of the human psyche. The writer masterfully uses the possibilities of artistic language, reflecting his tastes and worldview in his works. The ideological and aesthetic effect of a work depends on the interrelation of its various components. There is a narrative device in the structure of the novel, covering several aspects related to the form of the work. A special genre of fiction was created to study an individual as a value, more complex and unique than the outside world. A new era in literature has arisen, Togai Murod has introduced a non-standard style to our literature.